2014
DOI: 10.1111/epi.12758
|View full text |Cite
|
Sign up to set email alerts
|

Birth outcomes after prenatal exposure to antiepileptic drugs—A population‐based study

Abstract: SUMMARYObjective: We studied the potential impact of antiepileptic drugs (AEDs) on fetal growth and gestational age at birth. Methods: In the Danish Medical Birth Registry, we identified all pregnancies with birth outcomes from 1997 to 2008 and linked with data from the Danish National Prescription Register. We used binomial regression to study preterm birth (<37 weeks), low birth weight (<2,500 g), and small for gestational age (SGA), adjusted for potential confounding factors including maternal age, smoking,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 23 publications
6
58
2
2
Order By: Relevance
“…When studied as a single group, infants with intrauterine growth restriction, irrespective of cause, have increased mortality and morbidity [10]. The differences in ponderal index, birth weight and SGA in this study were mostly small, but significant and in line with other studies [2,6,7]. However, to evaluate whether growth restrictions in infants of mothers with epilepsy are associated with later morbidity or neurocognitive deficiencies, more studies with extensive follow up are required.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…When studied as a single group, infants with intrauterine growth restriction, irrespective of cause, have increased mortality and morbidity [10]. The differences in ponderal index, birth weight and SGA in this study were mostly small, but significant and in line with other studies [2,6,7]. However, to evaluate whether growth restrictions in infants of mothers with epilepsy are associated with later morbidity or neurocognitive deficiencies, more studies with extensive follow up are required.…”
Section: Discussionsupporting
confidence: 79%
“…the indication for treatment, and this is unfortunately where registers with un-validated epilepsy diagnoses may fall short. Another factor in intra uterine growth is the maternal weight before and during pregnancy, a factor that has not been controlled for in recent studies [2,7]. An estimation of gestational age depends upon provision of a reliable date of last menstruation.…”
mentioning
confidence: 99%
“…Antiepileptic drugs are previously reported as risk factors for intrauterine growth retardation . It could be argued that low birth weight might be a confounding factor for acute CS in this study as it is a factor that is also associated with breech presentation and breech presentation is associated with acute CS.…”
Section: Discussionmentioning
confidence: 71%
“…One study identified in our literature search reported that the relative risk for the association between levetiracetam versus lamotrigine monotherapy and SGA was 1.3 (1.0 to 1.7 ) [16], which compares with the OR in our study for monotherapy or polytherapy combined: 1.3 (0.5 to 3.0). Comparisons with women unexposed to AEDs were less clear: one study reported that levetiracetam exposure was associated with shorter pregnancies and lighter infants [14], one reported lighter infants but practically null effects on duration of pregnancy and head circumference [20], and one reported protective effects for SGA and microcephaly [24]. The pooled risk for congenital malformations in subjects exposed to levetiracetam has been reported as similar to that for the unexposed, although some individual studies reported increased risk [4].…”
Section: Levetiracetammentioning
confidence: 99%